2018
DOI: 10.3934/dcdsb.2018158
|View full text |Cite
|
Sign up to set email alerts
|

A time-delay in the activator kinetics enhances the stability of a spike solution to the gierer-meinhardt model

Abstract: We study the spectrum of a new class of nonlocal eigenvalue problems (NLEPs) that characterize the linear stability properties of localized spike solutions to the singularly perturbed two-component Gierer-Meinhardt (GM) reaction-diffusion (RD) system with a fixed time-delay T in only the nonlinear autocatalytic activator kinetics. Our analysis of this model is motivated by the computational study of Seirin Lee et al. [Bull. Math. Bio., 72(8), (2010)] on the effect of gene expression time delays on spatial patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…However, these morphogens are often, though not always, signalling molecules which must be produced via gene transcription, leading to delays between uptake of a signal and the up-or downregulation of the resultant product. Such time delays have been studied in the past few decades [129,[198][199][200][201][202], broadly with the conclusion that they may lead to oscillatory behaviours, rather than the formation of stationary patterns (though see [203] for a case where delay can enhance the stability of spikes). Such results plausibly call into question the standard use of reaction-diffusion frameworks for the fastest cellular self-organization processes, where oscillations are not typically observed, though we caution that there is more work to be done both biologically and mathematically in testing these hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…However, these morphogens are often, though not always, signalling molecules which must be produced via gene transcription, leading to delays between uptake of a signal and the up-or downregulation of the resultant product. Such time delays have been studied in the past few decades [129,[198][199][200][201][202], broadly with the conclusion that they may lead to oscillatory behaviours, rather than the formation of stationary patterns (though see [203] for a case where delay can enhance the stability of spikes). Such results plausibly call into question the standard use of reaction-diffusion frameworks for the fastest cellular self-organization processes, where oscillations are not typically observed, though we caution that there is more work to be done both biologically and mathematically in testing these hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…However, these morphogens are often, though not always, signalling molecules which must be produced via gene transcription, leading to delays between uptake of a signal and the up or down regulation of the resultant product. Such time delays have been studied in the past few decades [54,62,63,92,121,211], broadly with the conclusion that they may lead to oscillatory behaviours, rather than the formation of stationary patterns (though see [55] for a case where delay can enhance the stability of spikes). Such results plausibly call into question the standard use of reaction-diffusion frameworks for the fastest cellular self-organisation processes, where oscillations are not typically observed, though we caution that there is more work to be done both biologically and mathematically in testing these hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…We repeated the process for different values of L and similar results are found in each case. In [5] it is found that this form of delay can actually aid in the stabilization of spike solutions. Simulations of (36) with delay values of up to 50 resulted in stable solutions with no oscillations.…”
Section: 5mentioning
confidence: 99%